Probing Efimov discrete scaling in an atom-molecule collision - Shalchi, M. A. [UNESP]; Yamashita, M. T. [UNESP]; Hadizadeh, M. R.; Garrido, E.; Tomio, Lauro [UNESP]; Frederico, T. (American Physical Society (APS), 2018)
The discrete Efimov scaling behavior, well known in the low-energy spectrum of three-body bound systems for large scattering lengths (unitary limit), is identified in the energy dependence of an atom-molecule elastic cross section in mass-imbalanced systems. That happens in the collision of a heavy atom with mass mH with a weakly bound dimer formed by the heavy atom and a lighter one with mass mLmH. Approaching the heavy-light unitary limit, the s-wave elastic cross section σ will present a sequence of zeros or minima at collision energies following closely the Efimov geometrical law. Our results, obtained with Faddeev calculations and supplemented by a Born-Oppenheimer analysis, open a perspective to detecting the discrete scaling behavior from low-energy scattering data, which is timely in view of the ongoing experiments with ultracold binary mixtures having strong mass asymmetries, such as lithium and cesium or lithium and ytterbium.